In Vivo Identification of Skin Photodamage Induced by Fractional CO2 and Picosecond Nd:YAG Lasers with Optical Coherence Tomography - Chau Yee Ng (Diagnostics, 2022)
Fractional laser treatment is commonly used for dermatological applications, enabling effective induction of collagen regeneration and significantly reducing recovery time. However, it is challenging to observe laser-induced photodamage beneath the tissue surface in vivo, making the non-invasive evaluation of treatment outcomes difficult. For in vivo real-time study of the photodamage induced by fractional pulsed CO2 and Nd:YAG lasers commonly utilized for clinical therapy, a portable spectral-domain optical coherence tomography (SD-OCT) system was implemented for clinical studies. The photodamage caused by two lasers, including photothermal and photoacoustic effects, was investigated using OCT, together with the correlation between photodamage and exposure energy. Additionally, to investigate the change in the optical properties of tissue due to photodamage, the attenuation coefficients and damaged areas of normal skin and laser-treated skin were estimated for comparison. Finally, the recovery of the exposed skin with both lasers was also compared using OCT. The results show that OCT can be a potential solution for in vivo investigation of laser-induced tissue damage and quantitative evaluation.